1998
DOI: 10.1093/emboj/17.11.3168
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic maturation in Xenopus requires polyadenylation of multiple mRNAs

Abstract: Cytoplasmic polyadenylation of specific mRNAs commonly is correlated with their translational activation during development. Here, we focus on links between cytoplasmic polyadenylation, translational activation and the control of meiotic maturation in Xenopus oocytes. We manipulate endogenous c-mos mRNA, which encodes a protein kinase that regulates meiotic maturation. We determined that translational activation of endogenous c-mos mRNA requires a long poly(A) tail per se, rather than the process of polyadenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 38 publications
2
61
0
1
Order By: Relevance
“…Barkoff et al (1998) reported that polyadenylation of mos mRNA is not sufficient for accumulation of the protein in the absence of progesterone. Moreover, when meiotic maturation is inhibited by the presence of kinase-inactive p34 cdc2 (K33R), mos mRNA is still polyadenylated in response to progesterone (Ballantyne et al, 1997) but the protein does not accumulate (Nebreda et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Barkoff et al (1998) reported that polyadenylation of mos mRNA is not sufficient for accumulation of the protein in the absence of progesterone. Moreover, when meiotic maturation is inhibited by the presence of kinase-inactive p34 cdc2 (K33R), mos mRNA is still polyadenylated in response to progesterone (Ballantyne et al, 1997) but the protein does not accumulate (Nebreda et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In some instances Complete-Mini (Boehringer Mannheim) protease inhibitor cocktail was substituted for these inhibitors. Clarification of oocyte homogenates was performed as described previously (4). Proteins were separated by electrophoresis through sodium dodecyl sulfate (SDS)-6.5 to 10% polyacrylamide gel electrophoresis (PAGE) gels (25) and then transferred electrophoretically to Immobilon-P (Millipore, Bedford, Mass.)…”
Section: Methodsmentioning
confidence: 99%
“…The ability of recombinant p33 ringo to induce MPF activation and GVBD independently of protein synthesis indicates that it does not function by stimulating the translation of maternal mRNAs encoding p39 mos or other triggering proteins (Barkoff et al 1998). Moreover, the observation that p42 mpk1 activation by p33 ringo is strongly reduced by the presence of cycloheximide suggests that p33…”
Section: Genes and Development 2183mentioning
confidence: 99%
“…In spite of the central role of p39 mos and the p42 mpk1 pathway in oocyte maturation, there is evidence that synthesis of other proteins in addition to p39 mos is also required for progesterone to initiate oocyte maturation (Nebreda et al 1995;Barkoff et al 1998). Thus, in many batches of oocytes, the ability of p39 mos or a constitutively active MAP kinase kinase mutant to activate pre-MPF is significantly reduced when protein synthesis is inhibited, whereas p42 mpk1 is normally activated under these conditions (Yew et al 1992;Daar et al 1993;Shibuya and Ruderman 1993;Huang et al 1995;Murakami and Vande Woude 1997).…”
mentioning
confidence: 99%